Therapeutic Prospects of Polysaccharides for Ovarian Cancer - Wang, Kaili; Cai, Mengcheng; Sun, Shuai; Cheng, Wen; Zhai, Dongxia; Ni, Zhexin; Yu, Chaoqin (Frontiers in Nutrition, 2022)
Ovarian cancer (OC) is ranked as the leading cause of death among cancers of the female reproductive tract. First-line platinum treatment faces the severe challenges associated with the patient relapse and poor prognosis. Thus, it is imperative to develop natural antitumor drugs for OC with high efficacy. Natural polysaccharides have significant biological activities and antitumor effects. Our work has demonstrated that polysaccharides play key roles by inhibiting the cell proliferation and growth, regulating the tumor cell cycle, inducing apoptosis, suppressing the tumor cell migration and invasion, improving the immunomodulatory activities, and enhancing the efficacy of chemotherapy (cisplatin) in OC, which provide powerful evidence for the application of polysaccharides as novel anticancer agents, supplementary remedies, and adjunct therapeutic agents alone or in combination with cisplatin for preventing and treating the OC.